Characterizing the plasma metabolome during 14 days of live‐high, train‐low simulated altitude: A metabolomic approach. Issue 1 (1st November 2018) - Lawler, Nathan G.; Abbiss, Chris R.; Gummer, Joel P. A.; Broadhurst, David I.; Govus, Andrew D.; Fairchild, Timothy J.; Thompson, Kevin G.; Garvican‐Lewis, Laura A.; Gore, Christopher J.; Maker, Garth L.; Trengove, Robert D.; Peiffer, Jeremiah J.
Abstract : New Findings: What is the central question of this study? Does 14 days of live‐high, train‐low simulated altitude alter an individual's metabolomic/metabolic profile? What is the main finding and its importance? This study demonstrated that ∼200 h of moderate simulated altitude exposure resulted in greater variance in measured metabolites between subject than within subject, which indicates individual variability during the adaptive phase to altitude exposure. In addition, metabolomics results indicate that altitude alters multiple metabolic pathways, and the time course of these pathways is different over 14 days of altitude exposure. These findings support previous literature and provide new information on the acute adaptation response to altitude. Abstract: The purpose of this study was to determine the influence of 14 days of normobaric hypoxic simulated altitude exposure at 3000 m on the human plasma metabolomic profile. For 14 days, 10 well‐trained endurance runners (six men and four women; 29 ± 7 years of age) lived at 3000 m simulated altitude, accumulating 196.4 ± 25.6 h of hypoxic exposure, and trained at ∼600 m. Resting plasma samples were collected at baseline and on days 3 and 14 of altitude exposure and stored at −80°C. Plasma samples were analysed using liquid chromatography–high‐resolution mass spectrometry to construct a metabolite profile of altitude exposure. Mass spectrometry of plasma identified 36 metabolites, of which eight were statistically significant (false discovery rate probability 0.1) from baseline to either day 3 or day 14. Specifically, changes in plasma metabolites relating to amino acid metabolism (tyrosine and proline), glycolysis (adenosine) and purine metabolism (adenosine) were observed during altitude exposure. Principal component canonical variate analysis showed significant discrimination between group means ( P  < 0.05), with canonical variate 1 describing a non‐linear recovery trajectory from baseline to day 3 and then back to baseline by day 14. Conversely, canonical variate 2 described a weaker non‐recovery trajectory and increase from baseline to day 3, with a further increase from day 3 to 14. The present study demonstrates that metabolomics can be a useful tool to monitor metabolic changes associated with altitude exposure. Furthermore, it is apparent that altitude exposure alters multiple metabolic pathways, and the time course of these changes is different over 14 days of altitude exposure. Abstract :